(untitled) (Eurasian Journal of Ecology, 2016)
We isolated oxidizing microorganisms on developed by us agar medium which contains oil emulgaited by Triton X-100. It was established that oil destruction is carried out by microorganisms consortium but not single species. The study of microorganisms composition consortium showed that there are representatives of the next genera: Bacillus, micromycetes, and yeasts.